Kilonova/Macronova Emission from Compact Binary Mergers - Masaomi Tanaka (Advances in Astronomy)
We review current understanding of kilonova/macronova emission from compact binary mergers (mergers of two neutron stars or a neutron star and a black hole). Kilonova/macronova is emission powered by radioactive decays of r-process nuclei and it is one of the most promising electromagnetic counterparts of gravitational wave sources. Emission from the dynamical ejecta of ~0.01M⊙ is likely to have a luminosity of ~1040–1041 erg s−1 with a characteristic timescale of about 1 week. The spectral peak is located in red optical or near-infrared wavelengths. A subsequent accretion disk wind may provide an additional luminosity or an earlier/bluer emission if it is not absorbed by the precedent dynamical ejecta. The detection of near-infrared excess in short GRB 130603B and possible optical excess in GRB 060614 supports the concept of the kilonova/macronova scenario. At 200 Mpc distance, a typical peak brightness of kilonova/macronova with 0.01M⊙ ejecta is about 22 mag and the emission rapidly fades to >24 mag within ~10 days. Kilonova/macronova candidates can be distinguished from supernovae by (1) the faster time evolution, (2) fainter absolute magnitudes, and (3) redder colors. Since the high expansion velocity (v~0.1–0.2c) is a robust outcome of compact binary mergers, the detection of smooth spectra will be the smoking gun to conclusively identify the gravitational wave source.